Chronic extensor hallucis longus tendon rupture treated with double-bundle autograft of extensor hallucis capsularis: A case report - Toshinori Kurashige (SAGE Open Medical Case Reports, 2019)
The extensor hallucis capsularis is an accessory extensor tendon with varied occurrence. Here, we present the case of a 40-year-old man with chronic extensor hallucis longus tendon rupture treated using extensor hallucis capsularis tendon as a double-bundle autograft. He had dropped a knife proximal to the right hallux metatarsophalangeal joint 4 months ago. Computed tomography revealed the presence of extensor hallucis capsularis, with its width and thickness, and the point of divergence from the extensor hallucis longus tendon. Because direct suturing was considered difficult and the extensor hallucis capsularis tendon was sufficiently wide and long, double-bundle autograft transplantation of extensor hallucis capsularis was performed. At 1-year follow-up examination, the patient retained almost full function of his hallux. To the best of our knowledge, this is the first case to use this technique. Using the extensor hallucis capsularis tendon for grafting should be carefully considered because the variable width and length may limit the graft strength. Level of evidence: IV